2023
DOI: 10.3390/microorganisms11030646
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functional Grape Juices Fortified with Free or Immobilized Lacticaseibacillus rhamnosus OLXAL-1

Abstract: During the last decade, a rising interest in novel functional products containing probiotic microorganisms has been witnessed. As food processing and storage usually lead to a reduction of cell viability, freeze-dried cultures and immobilization are usually recommended in order to maintain adequate loads and deliver health benefits. In this study, freeze-dried (free and immobilized on apple pieces) Lacticaseibacillus rhamnosus OLXAL-1 cells were used to fortify grape juice. Juice storage at ambient temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
2
6
0
Order By: Relevance
“…The incorporation of immobilized probiotic cells resulted in higher cell viability compared to the cheese sample fortified with free cells, indicating the positive impact of cell immobilization on the maintenance of high cell loads. These results are in accordance with previous studies that demonstrated the enhancement of cell survival by cell immobilization [4,32,33]. Indeed, the incorporation of immobilized L. casei ATCC 393 on apple pieces and casein in yogurt resulted in cell loads > 7 logcfu/g up to 28 days of storage [32], while Shehata et al (2022) reported that soft cheese with immobilized L. paracasei cells on wheat bran exhibited high cell loads (>7.5 logcfu/g) after 30 days of storage [33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The incorporation of immobilized probiotic cells resulted in higher cell viability compared to the cheese sample fortified with free cells, indicating the positive impact of cell immobilization on the maintenance of high cell loads. These results are in accordance with previous studies that demonstrated the enhancement of cell survival by cell immobilization [4,32,33]. Indeed, the incorporation of immobilized L. casei ATCC 393 on apple pieces and casein in yogurt resulted in cell loads > 7 logcfu/g up to 28 days of storage [32], while Shehata et al (2022) reported that soft cheese with immobilized L. paracasei cells on wheat bran exhibited high cell loads (>7.5 logcfu/g) after 30 days of storage [33].…”
Section: Discussionsupporting
confidence: 91%
“…The acids found at increased concentrations in the KFP and KIP samples were sorbic, octanoic and decanoic acid, which were at higher amounts in the KFP samples-results that are in accordance with previous studies in dairy products fortified with probiotics [33,34]. Among alcohols, the most abundant were 3-methyl-1-butanol and 2-phenylethanol in all samples and are described as exerting malt notes and burnt aroma [4]. Carbonyl compounds detected in cheese samples belong to aldehydes and ketones, but aldehydes were in low concentrations due to their reduction to alcohols [35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nikolaou et al [ 12 ] investigated freeze-dried Lacticaseibacillus rhamnosus OLXAL-1 cells, free and immobilized on apple pieces, to fortify grape juice. The results showed that refrigerated storage resulted in cell loads > 7 log cfu/g for both free and immobilized cells for up to 10 days, achieving populations > 10 9 cfu per share, with no noticeable spoilage.…”
mentioning
confidence: 99%